Implementation of Caring Leadership Model Had an Effect on Nurse’s Burnout - Ni Made Nopita Wati; Hasib Ardani; Luky Dwiantoro (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2017)
The high demand for role and function as a nurse can potentially lead to burnout.The impact of burnout causes patients to have secondary infections that are not caused by the disease, decrease patient satisfaction and quality of care and mortality. Efforts that can be done to reduce the nurse's burnout is through the application of an effective leadership style. Caring leadership as a leadership style can facilitate the needs of nurses so that it will improve performance. This study aims to determine the effect of caring leadership of the head of space on the burnout of nurses. The method used is quasi experiment pre and post design with control group. A total of 46 nurses were taken as samples through purposive sampling fron 426 nurses. Data analysis using pairred t-test. The results showed that there was difference of average burnout value before and after applied caring leadership with p-value=0.000, which means there is influence of head room caring leadership against nurse's burnout. Implementation of caring leadership should be done consistently for all nursing activities in the hospital, given the caring leadership can reduce the burnout of nurses that will ultimately have an impact on the quality of nursing services.